Does the Chronicity of Anterior Cruciate Ligament Ruptures Influence Patient-Reported Outcomes Before Surgery?. (March 2017) - Nguyen, Joseph T.; Wasserstein, David; Reinke, Emily K.; Spindler, Kurt P.; Mehta, Nabil; Doyle, John B.; ,; Marx, Robert G.
Background: The time between an anterior cruciate ligament (ACL) injury and ACL reconstruction (ACLR) may influence baseline knee-related and general health-related patient-reported outcome measures (PROMs). Despite the common use of PROMs as main outcomes in clinical studies, this variable has never been evaluated. Purpose: To compare baseline health-related quality of life measures and the prevalence/pattern of meniscal and articular cartilage lesions between patients who underwent acute and chronic ACLR so as to provide clinicians with benchmark PROMs in 2 different patient populations with ACL injuries. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 1192 patients from the MOON (Multicenter Orthopaedic Outcomes Network) cohort who underwent primary ACLR were eligible. "Acute" ACLR was defined as <3 months (n = 853; 71.6%) and "chronic" ACLR as >6 months (n = 339; 28.4%) from injury. Patient demographics, surgical characteristics (articular cartilage injury, medial meniscal [MM] and lateral meniscal [LM] tears), and baseline PROM scores (Marx activity rating scale, International Knee Documentation Committee [IKDC] subjective form, Knee injury and Osteoarthritis Outcome Score [KOOS], and Short Form–36 Health Survey [SF-36]) were collected to determine whether the time from injury to ACLR influences (1) baseline PROMs and (2) the pattern and prevalence of concurrent articular cartilage and meniscal injuries. Analysis of covariance models were used to adjust for confounders on baseline outcome scores (age, sex, body mass index [BMI], smoking status, competition level, education). Results: The median patient age was 23 years (interquartile range [IQR], 17-35 years), 530 (44.5%) were female, and the median BMI was 25.0 kg/m 2 (IQR, 22.3-27.9 kg/m 2 ); however, the chronic group was older, had a higher BMI, and consisted of fewer collegiate athletes. A significantly greater number of partial LM tears were seen in the acute group versus the chronic group (14.2% vs 6.5%, respectively; P < .001), but there were more meniscal tears overall (73.5% vs 63.2%, respectively; P = .001), complete MM tears (49.0% vs 22.5%, respectively; P < .001), and articular cartilage injuries (54.0% vs 32.8%, respectively; P < .001) in the chronic group versus the acute group. After controlling for confounders, patients in the chronic ACLR group reported a significantly lower baseline Marx score (7.75 vs 12.10, respectively; P < .001) but higher baseline IKDC, SF-36 physical functioning, and all KOOS subscale scores except the KOOS–quality of life subscale score compared to those in the acute ACLR group; however, only the KOOS–sports and recreation subscale exceeded the minimum clinically importance difference of 8 points (62.30 vs 48.26, respectively; P < .001). Conclusion: After controlling for age, sex, competition level, smoking, and BMI, patients in the chronic ACLR group participated in less pivoting and cutting sports but reported better pain/function. Whether decreased activity is deliberate after an ACL injury or patients who undergo chronic ACLR are simply less active and may be treated successfully without surgery warrants further investigation. Nonrandomized studies that utilize PROMs should consider time from injury in study design and data interpretation.